Interferon-gamma impairs phagocytosis of Escherichia coli by primary murine peritoneal macrophages stimulated with LPS and differentially modulates proinflammatory cytokine release. Issue 3 (September 2021) - Schütze, Sandra; Kaufmann, Annika; Bunkowski, Stephanie; Ribes, Sandra; Nau, Roland
Highlights: IFN-γ reduces the phagocytosis of E. coli by LPS-stimulated peritoneal macrophages. IFN-γ differentially modulates macrophage release of the TNF-α, IL-6, and KC. IFN-γ reduces KC release by macrophages stimulated by agonists of TLR2, 4, and 9. Elevated levels of IFN-γ might lead to reduced E. coli clearance during infections. Abstract: Introduction: Interferon-γ levels are increased upon viral infections and during inflamm-aging. Resistance to infections due to Escherichia coli ( E. coli ), a major cause of bacteriaemia and sepsis, is impaired in aged individuals, partly due to altered phagocytic capacity and cytokine release of immune cells. Here, we analyzed the effect of IFN-γ on phagocytosis of E. coli K1 and release of proinflammatory cytokines by macrophages in resting condition and upon stimulation with different bacterial Toll-like receptor (TLR) agonists. Methods: Primary peritoneal macrophages from C57BL/6 mice were exposed to medium or stimulated with agonists of TLR4 (LPS), 1/2 (Pam3 CSK4 ), and 9 (CpG-DNA) in the presence and absence of IFN-γ (100 U/ml) for 24 h. TNF-α, IL-6, and KC were measured in the cell culture supernatant by ELISA. Macrophages were exposed to viable E. coli K1. After 90 min, intracellular phagozytosed bacteria were quantified by quantitative plating. Results: Macrophages treated with LPS 1 µg/ml in the presence of IFN-γ ingested more than 10-fold lower numbers of E. coli than macrophages treated with LPS alone. Phagocytosis of E. coli by macrophages in resting condition or upon stimulation with Pam3 CSK4 or CpG was not significantly affected by IFN-γ. Cytokine release was differentially modulated by IFN-γ, with reduced KC release by TLR-stimulated macrophages in the presence of IFN-γ being the most striking effect. Conclusions: In vitro, IFN-γ reduces the phagocytosis of E. coli by LPS-stimulated macrophages and differentially modulates cytokine release of macrophages activated by different bacterial TLR agonists. Elevated levels of IFN-γ might lead to reduced bacterial clearance and worse outcome of bacterial infections, e.g., in aged individuals and after viral infections and other inflammatory events.